Preparation method of iron-based perovskite oxide and application of iron-based perovskite oxide in electrocatalytic reduction of nitrate to synthesize ammonia

By designing an iron-based perovskite oxide catalyst, the performance bottleneck of existing electrocatalysts in the process of nitrate reduction to ammonia synthesis was solved, realizing a highly efficient and simple electrocatalytic conversion of nitrate to ammonia, with catalytic activity superior to commercial iron oxide.

CN121342089APending Publication Date: 2026-01-16NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511440488.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-10
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing electrocatalysts face performance bottlenecks in the nitrate reduction to ammonia synthesis process, making it difficult to balance activity, selectivity, and cost, and they are prone to generating byproducts. The similar reduction potentials of HER and NO3RR lead to fierce competition.

Method used

A class of iron-based perovskite oxide catalysts was designed. High-density active sites were exposed and proton transport channels were optimized through a controllable synthesis strategy. The materials were prepared using simple processes such as the sol-gel method. The material structure is ABO3-δ and AA'BB'O6, with rare earth or alkali metals at the A site, iron at the B site, and molybdenum at the B' site.

Benefits of technology

The method achieves highly efficient electrocatalytic reduction of nitrate to ammonia, with catalytic activity superior to commercial iron oxide. The preparation process is simple and reproducible, and it exhibits excellent electrocatalytic conversion performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121342089A_ABST
    Figure CN121342089A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based perovskite oxide catalyst for synthesizing ammonia through nitrate electrocatalytic reduction. The structural general formula of the iron-based perovskite oxide catalyst is ABO3-delta (0 < = delta < = 1) and AA 'BB' O6. Wherein the A site of the ABO3-delta (0 < = delta < = 1) type perovskite oxide is composed of rare earth or alkali metal elements, and the B site is composed of an iron element. An A site and an A'site of the AA 'BB' O6 type perovskite oxide are respectively composed of a rare earth element and an alkali metal element, a B site is an iron element, and a B 'site is a molybdenum element. The catalyst shows nitrate reduction reaction (NO3RR) activity superior to that of a commercial iron oxide material in alkaline electrolyte, and the enhanced catalytic effect of the catalyst is derived from remarkably improved reaction mass transfer efficiency and active site density. Experimental results show that the catalyst system has excellent cycle stability and operation durability, and keeps stable catalytic performance under continuous operation conditions. The invention provides a novel catalytic material solution with practical value for water nitrate pollution abatement and green ammonia synthesis technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalytic reduction of nitrate to ammonia synthesis technology, specifically involving the application of a class of iron-based perovskite oxide materials in electrocatalytic reduction of nitrate to ammonia synthesis. Background Technology

[0002] Ammonia (NH3), one of the world's most produced chemical products, is widely used in fertilizer production, pharmaceuticals, and clean energy storage. Currently, industrial-scale NH3 synthesis mainly relies on the Haber-Bosch process, which operates under high temperature and pressure (300–500°C, 150–200 atm), consuming approximately 1.8% of global energy supply and contributing 1.3% of CO2 emissions. In recent years, electrocatalytic nitrate reduction to ammonia (NO3RR-to-NH3) has been considered a disruptive technology to replace traditional processes due to its mild reaction conditions (ambient temperature and pressure), wide availability of raw materials (wastewater nitrates), and zero carbon emissions. However, the industrialization of NO3RR-to-NH3 is limited by catalyst performance bottlenecks: nitrate reduction involves a complex eight-electron transfer pathway, easily generating byproducts such as nitrite and hydroxylamine (NH2OH); simultaneously, HER and NO3RR have similar reduction potentials (-0.2 to -0.8 V vs. RHE), leading to fierce competition between the two. While existing catalysts (such as noble metals, transition metal oxides and carbon-based composites) can partially alleviate the above problems, it is still difficult to balance activity, selectivity and cost-effectiveness.

[0003] Therefore, to address the aforementioned issues, designing catalyst materials with abundant exposed active sites and efficient proton transport channels to suppress byproduct formation and optimize proton supply is a core direction for future research. Summary of the Invention

[0004] To address the aforementioned problems, this invention synthesizes a class of iron-based perovskite oxide electrocatalytic materials. This material achieves high-density exposure of active sites through a controllable synthesis strategy, while also possessing the advantages of simple preparation process, low cost, and low energy consumption, demonstrating its potential application value as a highly efficient nitrate reduction electrocatalytic material.

[0005] To achieve the above-mentioned objective, the first aspect of the present invention provides: A class of iron-based perovskite oxides with the general structural formula ABO 3-δ (0≤δ≤1) and AA'BB'O6. Where ABO 3-δ In (0≤δ≤1) type perovskite oxides, the A-site is composed of rare earth or alkali metal elements, and the B-site is composed of iron. In AA'BB'O6 type perovskite oxides, the A and A' sites are composed of rare earth elements and alkali metal elements, respectively, the B-site is composed of iron, and the B' site is composed of molybdenum.

[0006] In one embodiment, the molecular formula of the perovskite oxide is ABO. 3-δ (0≤δ≤1); wherein the preferred elements at site A are La and Sr; and the preferred element at site B is Fe. The molecular formula of the double perovskite oxide is AA'BB'O6; wherein the preferred elements at site A are La, Pr, Nd, Sm, and Gd; the preferred elements at site A' are Ca, Sr, and Ba; the preferred elements at site B are Fe; and the preferred element at site B' is Mo.

[0007] In one embodiment, the iron-based perovskite oxide is LaFeO. 3-δ La 0.4 Sr 0.6 FeO 3-δ La 0.5 Ba 0.5 FeO 3-δ Pr 0.5 Ba 0.5 FeO 3-δ 、Nd 0.5 Ba 0.5 FeO 3-δ 、Sm 0.5 Ba 0.5 FeO 3-δ Gd 0.5 Ba 0.5 FeO 3-δ NdBaFe2O 5+δ SmBaFe2O 5+δ Ca2FeMoO6, Sr2FeMoO6 and Ba2FeMoO6.

[0008] The second aspect of the invention provides: The above-mentioned iron-based perovskite oxides are prepared by methods such as solid-state reaction, sol-gel method, co-precipitation method, combustion method, hydrothermal method, or microwave method according to the stoichiometric ratio.

[0009] In one embodiment, it is prepared by the sol-gel method.

[0010] In one embodiment, the steps of the sol-gel method include: dissolving the nitrate of the A-site element and the nitrate of the B-site element or ammonium molybdate in deionized water according to the stoichiometric ratio, adding citric acid (CA) and ethylenediaminetetraacetic acid (EDTA), heating and stirring until a viscous gel is obtained, heating and drying the obtained gel to obtain a fluffy dry gel, grinding and calcining it.

[0011] In one embodiment, the gel is heated and dried at 200°C for 5 hours.

[0012] In one embodiment, the calcination temperature in air is 800~1100℃ and the calcination time is 5~10h; for AA'BB'O6 type perovskite oxide, it is further calcined at 600~1100℃ for 4~10h in a 5%H2 / 95%Ar mixed atmosphere.

[0013] A second aspect of the present invention provides the application of the above-described iron-based perovskite oxide in the electrocatalytic reduction of nitrate to ammonia.

[0014] The advantages of the invention compared to existing technologies are as follows: The electrocatalyst for the electrocatalytic reduction of nitrate of this invention achieves the purpose of regulating and optimizing the performance of nitrate reduction to ammonia by replacing the metal at the A site. It exhibits excellent electrocatalytic conversion performance of nitrate to ammonia, and its catalytic activity is superior to that of commercial iron oxide. The iron-based perovskite oxide involved in this invention can be prepared using traditional sol-gel methods, solid-phase reaction methods, etc. The material preparation process is simple and has good reproducibility, and has potential value for practical application. Attached Figure Description

[0015] Figure 1 LaFeO in Example 1 of this invention 3-δ X-ray diffraction (XRD) curves of the catalyst; Figure 2 LaFeO in Example 1 of this invention 3-δ LSV curves of the catalyst in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution; Figure 3 LaFeO in Example 1 of this invention 3-δ The electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + Yield plot; Figure 4 La in Embodiment 2 of the present invention 0.4 Sr 0.6 FeO 3-δ X-ray diffraction (XRD) curves of the catalyst; Figure 5 La in Embodiment 2 of the present invention 0.4 Sr 0.6 FeO 3-δ LSV curves of the catalyst in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution; Figure 6 La in Embodiment 2 of the present invention 0.4 Sr 0.6 FeO 3-δThe electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + Yield plot; Figure 7 Nd in Example 3 of this invention 0.5 Ba 0.5 FeO 3-δ X-ray diffraction (XRD) curves of the catalyst; Figure 8 Nd in Example 3 of this invention 0.5 Ba 0.5 FeO 3-δ LSV curves of the catalyst in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution; Figure 9 Nd in Example 3 of this invention 0.5 Ba 0.5 FeO 3-δ The electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + Yield plot; Figure 10 Sm in Embodiment 4 of this invention 0.5 Ba 0.5 FeO 3-δ X-ray diffraction (XRD) curves of the catalyst; Figure 11 Sm in Embodiment 4 of this invention 0.5 Ba 0.5 FeO 3-δ LSV curves of the catalyst in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution; Figure 12 Sm in Embodiment 4 of this invention 0.5 Ba 0.5 FeO 3-δ The electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + Yield plot; Figure 13 NdBaFe2O in Example 5 of this invention 5+δ X-ray diffraction (XRD) curves of the catalyst; Figure 14 NdBaFe2O in Example 5 of this invention 5+δ LSV curves of the catalyst in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution; Figure 15 NdBaFe2O in Example 5 of this invention 5+δ The electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + Yield plot; Figure 16 SmBaFe2O in Example 6 of this invention 5+δ X-ray diffraction (XRD) curves of the catalyst; Figure 17 SmBaFe2O in Example 6 of this invention 5+δ LSV curves of the catalyst in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution; Figure 18 SmBaFe2O in Example 6 of this invention 5+δ The electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + Yield plot; Figure 19 This is an X-ray diffraction (XRD) curve of the Ca2FeMoO6 catalyst in Example 7 of this invention; Figure 20 The LSV curves of the Ca2FeMoO6 catalyst in Example 7 of this invention in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution are shown. Figure 21 The product NH4 is obtained from the electrocatalytic reduction of nitrate by the Ca2FeMoO6 catalyst in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution in Example 7 of this invention. + Yield plot; Figure 22 This is an X-ray diffraction (XRD) curve of the Sr2FeMoO6 catalyst in Example 8 of this invention; Figure 23 The LSV curves of the Sr2FeMoO6 catalyst in Example 8 of this invention in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution are shown. Figure 24 The Sr2FeMoO6 catalyst in Example 8 of this invention is used for the electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution to produce NH4. + Yield plot; Figure 25 This is an X-ray diffraction (XRD) curve of the Ba2FeMoO6 catalyst in Example 9 of this invention; Figure 26 The LSV curves of the Ba2FeMoO6 catalyst in Example 9 of this invention in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution are shown. Figure 27 The NH4+ produced by the electrocatalytic reduction of nitrate using the Ba2FeMoO6 catalyst in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution in Example 9 of this invention. + The yield chart.

[0016] Figure 28 This is an X-ray diffraction (XRD) curve of the commercial Fe2O3 catalyst in Comparative Example 1 of this invention; Figure 29 The LSV curves of the commercial Fe2O3 catalyst in Comparative Example 1 of this invention in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution are shown. Figure 30 The product NH4 is obtained from the electrocatalytic reduction of nitrate using a commercial Fe2O3 catalyst in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution, as described in Comparative Example 1 of this invention. + The yield chart. Detailed Implementation

[0017] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0018] This invention provides a class of iron-based perovskite oxides with the general structural formula ABO. 3-δ (0≤δ≤1) and AA'BB'O6. Where ABO 3-δ In (0≤δ≤1) type perovskite oxides, the A-site is composed of rare earth or alkali metal elements, and the B-site is composed of iron. In AA'BB'O6 type perovskite oxides, the A and A' sites are composed of rare earth elements and alkali metal elements, respectively, the B-site is composed of iron, and the B' site is composed of molybdenum.

[0019] In one embodiment, the molecular formula of the perovskite oxide is ABO. 3-δ (0≤δ≤1); wherein the preferred elements at site A are La and Sr; and the preferred element at site B is Fe. The molecular formula of the double perovskite oxide is AA'BB'O6; wherein the preferred elements at site A are La, Pr, Nd, Sm, and Gd; the preferred elements at site A' are Ca, Sr, and Ba; the preferred elements at site B are Fe; and the preferred element at site B' is Mo.

[0020] In one embodiment, the iron-based perovskite oxide is LaFeO. 3-δ La 0.4 Sr 0.6 FeO 3-δ La 0.5 Ba 0.5 FeO 3-δ Pr 0.5 Ba 0.5 FeO 3-δ 、Nd 0.5 Ba 0.5 FeO 3-δ 、Sm 0.5 Ba 0.5 FeO 3-δ Gd 0.5 Ba 0.5 FeO 3-δ NdBaFe2O 5+δ SmBaFe2O 5+δ Ca2FeMoO6, Sr2FeMoO6 and Ba2FeMoO6.

[0021] The catalyst material of this invention can be synthesized using the sol-gel method, or prepared using solid-phase reaction, co-precipitation, combustion, hydrothermal, or microwave methods. The preparation method of the material of this invention will be described below using the sol-gel method as an example.

[0022] The above-mentioned iron-based perovskite oxides are prepared by methods such as solid-state reaction, sol-gel method, co-precipitation method, combustion method, hydrothermal method, or microwave method according to the stoichiometric ratio.

[0023] According to the target product ABO 3-δ The elemental ratios of the chemical formulas (0≤δ≤1) and AA'BB'O6 were determined by weighing out the stoichiometric ratios. The nitrates of the A-site element and the nitrates of the B-site element, or ammonium molybdate, were dissolved in deionized water. Citric acid (CA) and ethylenediaminetetraacetic acid (EDTA) were added, and the mixture was heated and stirred at 200°C until a viscous gel was obtained. The resulting gel was dried at 200°C for 5 hours to obtain a fluffy dry gel. After grinding, it was calcined in air at 800–1100°C for 5–10 hours. For AA'BB'O6 type perovskite oxide, it was further calcined at 600–1100°C for 4–10 hours in a 5% H2 / 95% Ar mixed atmosphere to obtain the desired ABO. 3-δ (0≤δ≤1) and AA'BB'O6 material powder.

[0024] The process of preparing an electrode using the catalyst prepared in this invention and evaluating the electrode's electrocatalytic reduction of nitrate (NO3RR) is as follows: Preparation of catalyst slurry: ABO 3-δ (0≤δ≤1) and AA'BB'O6 powder are mixed with a certain amount of conductive carbon black (conductive carbon black mass fraction 10%~90%, which plays the role of conduction and support, and has almost no catalytic effect) and dispersed in ethanol or other organic solvents. Then, an appropriate amount of Nafion (mass fraction 5%) solution is added to it (catalyst concentration is 1~10mg / mL, Nafion concentration in solution is 0.2~2mg / mL), and then ultrasonic vibration is used to mix evenly to obtain the slurry for preparing the catalyst.

[0025] Electrode preparation: A certain amount of the catalyst slurry prepared above was transferred onto commercial carbon paper using a microsyringe, so that its loading on the commercial carbon paper was 1~3 mg / cm³. 2 Then, let it air dry at ambient temperature.

[0026] Electrode activity measurement: The prepared electrode was placed in an H-type cell for electrochemical testing.

[0027] The testing process is as follows: The electrochemical testing system was a three-electrode system (commercial carbon paper with catalyst supported as the working electrode, platinum sheet or platinum wire as the counter electrode, and Hg / HgO as the reference electrode), and the electrolytes were 0.1 mol / L KOH solution and 500 mg / L KNO3 solution.

[0028] Before testing, argon gas was continuously introduced into the reactor for 30-60 minutes to ensure that the electrolyte solution was saturated with argon gas. The gas flow rate was 150-250 mL / min. The argon gas flow was maintained during the test.

[0029] After activation for 1000 seconds at -0.6V vs. RHE potential, the data was recorded using linear sweep voltammetry (LSV) at a scan rate of 5mV / s. Electrocatalytic testing was performed using chronoamperometry for 1 hour.

[0030] The catalysts designed in this invention include, but are not limited to, the catalysts in the following embodiments, and the preparation methods involved include, but are not limited to, the preparation methods in the following embodiments.

[0031] Example 1: LaFeO 3-δ Catalyst preparation and evaluation of electrocatalytic nitrate reduction catalytic activity; LaFeO 3-δThe catalyst powder was synthesized via a sol-gel method. Stoichiometric amounts of La(NO3)3·6H2O (analytical grade) and Fe(NO3)3·9H2O (analytical grade) were weighed out and dissolved in deionized water. Citric acid (CA) and ethylenediaminetetraacetic acid (EDTA) were added as complexing agents. The resulting mixture was continuously stirred on a heating platform at 200°C until a viscous gel was obtained. The gel was dried in a drying oven at 200°C for 5 hours to completely dry the gel, yielding a fluffy black dry gel. The dry gel was thoroughly ground in a mortar until completely homogeneous. The ground product was calcined in air at 800°C for 5 hours to obtain the desired LaFeO. 3-δ Catalyst powder. Figure 1 The X-ray diffraction (XRD) curves shown indicate the successful synthesis of perovskite-structured LaFeO. 3-δ Catalyst powder.

[0032] Evaluation of the electrocatalytic reduction performance of the catalyst for nitrate. Weigh 5-10 mg of LaFeO. 3-δ The catalyst, preferably 6 mg, is dispersed with 1-2 mg of conductive carbon black (SuperP), preferably 1.5 mg, in 900-1000 μL of ethanol, preferably 940 μL. Then, 50-100 μL of Nafion (4-6% by mass, preferably 5%) solution, preferably 60 μL, is added. The mixture is ultrasonically vibrated for 0.5-1 h to obtain a homogeneous catalyst slurry, preferably 0.5 h. Then, 50-200 μL, preferably 90 μL, of the catalyst slurry is transferred using a microsyringe onto commercial carbon paper with a diameter of 0.5 × 0.5 cm, and allowed to air dry naturally for 0.2-2 h, preferably 1 h. The resulting electrode is then subjected to an electrocatalytic reduction of nitrate catalytic performance evaluation according to the electrode testing procedure described above.

[0033] Figure 2 The LaFeO prepared in Example 1 3-δ Polarization curves in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution. Figure 3 The LaFeO prepared in Example 1 3-δ The electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + The yield diagram shows that, within a certain overpotential range, LaFeO 3-δ The yield and Faraday efficiency at the optimal potential (-0.4 V vs. RHE) are 0.374 mgh. -1 cm -2 The concentration was 76.91%, indicating good electrocatalytic activity for the reduction of nitrates.

[0034] Example 2La 0.4 Sr 0.6 FeO 3-δ Catalyst preparation and evaluation of electrocatalytic nitrate reduction catalytic activity; La 0.4 Sr 0.6 FeO 3-δ The catalyst powder was synthesized via a sol-gel method. Stoichiometric amounts of La(NO3)3·6H2O (analytical grade), Sr(NO3)2, and Fe(NO3)3·9H2O (analytical grade) were weighed and dissolved in deionized water, with citric acid (CA) and ethylenediaminetetraacetic acid (EDTA) added as complexing agents. The resulting mixture was continuously stirred on a heating platform at 200°C until a viscous gel was obtained. The gel was then dried in a drying oven at 200°C for 5 hours to completely dry the substance, yielding a fluffy black dry gel. The dry gel was thoroughly ground in a mortar until completely homogeneous. The ground product was calcined in air at 800°C for 5 hours to obtain the desired La. 0.4 Sr 0.6 FeO 3-δ Catalyst powder. Figure 4 The X-ray diffraction (XRD) curves shown indicate the successful synthesis of La perovskite structure. 0.4 Sr 0.6 FeO 3-δ Catalyst powder.

[0035] Evaluation of the electrocatalytic reduction performance of the catalyst for nitrate. Electrode preparation and testing procedures were the same as in Example 1. Figure 5 La prepared in Example 2 0.4 Sr 0.6 FeO 3-δ Polarization curves in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution. Figure 6 La prepared in Example 2 0.4 Sr 0.6 FeO 3-δ The electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + The yield diagram shows that, within a certain overpotential range, La 0.4 Sr 0.6 FeO 3-δ The yield and Faraday efficiency at the optimal potential (-0.4 V vs. RHE) are 1.34 mgh. -1 cm -2 With a yield of 88.9%, it exhibits excellent electrocatalytic activity for the reduction of nitrates.

[0036] Example 3 Nd 0.5Ba 0.5 FeO 3-δ Catalyst preparation and evaluation of electrocatalytic nitrate reduction catalytic activity; Nd 0.5 Ba 0.5 FeO 3-δ The catalyst powder was synthesized via a sol-gel method. Stoichiometric amounts of Nd(NO3)3·6H2O (analytical grade), Ba(NO3)2, and Fe(NO3)3·9H2O (analytical grade) were weighed and dissolved in deionized water, with citric acid (CA) and ethylenediaminetetraacetic acid (EDTA) added as complexing agents. The resulting mixture was continuously stirred on a heating platform at 200°C until a viscous gel was obtained. The gel was then dried in a drying oven at 200°C for 5 hours to completely dry the gel, yielding a fluffy black dry gel. The dry gel was thoroughly ground in a mortar until completely homogeneous. The ground product was calcined in air at 1100°C for 5 hours to obtain the desired Nd2O3. 0.5 Ba 0.5 FeO 3-δ Catalyst powder. Figure 7 The X-ray diffraction (XRD) curves shown indicate the successful synthesis of perovskite-structured Nd2O3. 0.5 Ba 0.5 FeO 3-δ Catalyst powder.

[0037] Evaluation of the electrocatalytic reduction performance of the catalyst for nitrate. Electrode preparation and testing procedures were the same as in Example 1. Figure 8 The Nd prepared in Example 3 0.5 Ba 0.5 FeO 3-δ Polarization curves in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution. Figure 9 The Nd prepared in Example 3 0.5 Ba 0.5 FeO 3-δ The electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + The yield diagram shows that, within a certain overpotential range, Nd 0.5 Ba 0.5 FeO 3-δ The yield and Faraday efficiency at the optimal potential (-0.4 V vs. RHE) are 0.662 mgh. -1 cm -2 With a yield of 85.37%, it exhibits excellent electrocatalytic activity for the reduction of nitrates.

[0038] Example 4Sm 0.5 Ba 0.5FeO 3-δ Catalyst preparation and evaluation of electrocatalytic nitrate reduction catalytic activity; Sm 0.5 Ba 0.5 FeO 3-δ The catalyst powder was synthesized via a sol-gel method. Sm(NO3)3·6H2O (analytical grade), Ba(NO3)2, and Fe(NO3)3·9H2O (analytical grade) were weighed in stoichiometric proportions, dissolved in deionized water, and citric acid (CA) and ethylenediaminetetraacetic acid (EDTA) were added as complexing agents. The resulting mixture was continuously stirred on a heating plate at 200°C until a viscous gel was obtained. The gel was dried in a drying oven at 200°C for 5 hours to completely dry the gel, yielding a fluffy black dry gel. The dry gel was thoroughly ground in a mortar until completely homogeneous. The ground product was calcined in air at 1100°C for 5 hours to obtain the desired Sm. 0.5 Ba 0.5 FeO 3-δ Catalyst powder. Figure 10 The X-ray diffraction (XRD) curves shown indicate the successful synthesis of Sm perovskite structure. 0.5 Ba 0.5 FeO 3-δ Catalyst powder.

[0039] Evaluation of the electrocatalytic reduction performance of the catalyst for nitrate. Electrode preparation and testing procedures were the same as in Example 1. Figure 11 The Sm prepared in Example 4 0.5 Ba 0.5 FeO 3-δ Polarization curves in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution. Figure 12 The Sm prepared in Example 4 0.5 Ba 0.5 FeO 3-δ The electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + The yield diagram shows that, within a certain overpotential range, Sm 0.5 Ba 0.5 FeO 3-δ The yield and Faraday efficiency at the optimal potential (-0.4 V vs. RHE) are 0.6 mgh. -1 cm -2 With a yield of 92.11%, it exhibits excellent electrocatalytic activity for the reduction of nitrates.

[0040] Example 5 NdBaFe2O 5+δ Catalyst preparation and evaluation of electrocatalytic nitrate reduction catalytic activity; NdBaFe2O 5+δ The catalyst powder was synthesized via a sol-gel method. Stoichiometric amounts of Nd(NO3)3·6H2O (analytical grade), Ba(NO3)2, and Fe(NO3)3·9H2O (analytical grade) were weighed out and dissolved in deionized water. Citric acid (CA) and ethylenediaminetetraacetic acid (EDTA) were added as complexing agents. The resulting mixture was continuously stirred on a heating platform at 200°C until a viscous gel was obtained. The gel was dried in a drying oven at 200°C for 5 hours to completely dry the gel, yielding a fluffy black dry gel. The dry gel was thoroughly ground in a mortar until completely homogeneous. The ground product was calcined in air at 1100°C for 5 hours, followed by calcination at 850°C for 10 hours in a 5% H2 / 95% Ar mixed atmosphere to obtain the desired NdBaFe2O3. 5+δ Catalyst powder. Figure 13 The X-ray diffraction (XRD) curves shown indicate the successful synthesis of perovskite-structured NdBaFe2O3. 5+δ Catalyst powder.

[0041] Evaluation of the electrocatalytic reduction performance of the catalyst for nitrate. Electrode preparation and testing procedures were the same as in Example 1. Figure 14 The NdBaFe2O prepared in Example 5 5+δ Polarization curves in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution. Figure 15 The NdBaFe2O prepared in Example 5 5+δ The electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + The yield diagram shows that, within a certain overpotential range, NdBaFe2O 5+δ The yield and Faraday efficiency at the optimal potential (-0.4 V vs. RHE) are 0.333 mgh. -1 cm -2 The concentration was 72.28%, indicating good electrocatalytic activity for the reduction of nitrates.

[0042] Example 6 SmBaFe2O 5+δ Catalyst preparation and evaluation of electrocatalytic nitrate reduction catalytic activity; SmBaFe2O 5+δThe catalyst powder was synthesized via a sol-gel method. Sm(NO3)3·6H2O (analytical grade), Ba(NO3)2, and Fe(NO3)3·9H2O (analytical grade) were weighed in stoichiometric proportions, dissolved in deionized water, and citric acid (CA) and ethylenediaminetetraacetic acid (EDTA) were added as complexing agents. The resulting mixture was continuously stirred on a heating platform at 200°C until a viscous gel was obtained. The gel was dried in a drying oven at 200°C for 5 hours to completely dry the gel, yielding a fluffy black dry gel. The dry gel was thoroughly ground in a mortar until completely homogeneous. The ground product was calcined in air at 1100°C for 5 hours, and then calcined again at 850°C for 10 hours in a 5% H2 / 95% Ar mixed atmosphere to obtain the desired SmBaFe2O3. 5+δ Catalyst powder. Figure 16 The X-ray diffraction (XRD) curves shown indicate the successful synthesis of perovskite-structured SmBaFe2O 5+δ Catalyst powder.

[0043] Evaluation of the electrocatalytic reduction performance of the catalyst for nitrate. Electrode preparation and testing procedures were the same as in Example 1. Figure 17 The SmBaFe2O prepared in Example 6 5+δ Polarization curves in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution. Figure 18 The SmBaFe2O prepared in Example 6 5+δ The electrocatalytic reduction of nitrate in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution produces NH4+. + The yield diagram shows that, within a certain overpotential range, SmBaFe2O 5+δ The yield and Faraday efficiency at the optimal potential (-0.4 V vs. RHE) are 0.869 mgh. -1 cm -2 With a yield of 96.23%, it exhibits excellent electrocatalytic activity for the reduction of nitrates.

[0044] Example 7: Preparation of Ca2FeMoO6 catalyst and evaluation of its electrocatalytic activity in nitrate reduction; Ca2FeMoO6 catalyst powder was synthesized via a sol-gel method. Stoichiometric amounts of Ca(NO3)2, Fe(NO3)3·9H2O (analytical grade), and (NH4)6Mo7O were weighed separately. 24·4H2O was dissolved in deionized water, and citric acid (CA) and ethylenediaminetetraacetic acid (EDTA) were added as complexing agents. The resulting mixed solution was continuously stirred on a heating table at 200°C until a viscous gel was obtained. The obtained gel was dried in a drying oven at 200°C for 5 hours to completely dry the gel and obtain a fluffy black dry gel. The obtained dry gel was thoroughly ground in a mortar until it was completely mixed and homogeneous. The ground product was calcined in air at 800°C for 10 hours, and then calcined at 1050°C for 10 hours in a mixed atmosphere of 5%H2 / 95%Ar to obtain the desired Ca2FeMoO6 catalyst powder. Figure 19 The X-ray diffraction (XRD) curves shown indicate the successful synthesis of Ca2FeMoO6 catalyst powder with a double perovskite structure.

[0045] Evaluation of the electrocatalytic reduction performance of the catalyst for nitrate. Electrode preparation and testing procedures were the same as in Example 1. Figure 20 The polarization curves of Ca2FeMoO6 prepared in Example 7 in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution are shown. Figure 21 The product NH4 is obtained from the electrocatalytic reduction of nitrate by Ca2FeMoO6 prepared in Example 7 in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution. + The yield plot shows that, within a certain overpotential range, the yield and Faraday efficiency of Ca2FeMoO6 at the optimal potential (-0.4V vs. RHE) are 1.13 mgh. -1 cm -2 (Based on 2.16 mg cm -2 With a catalyst loading of 74.68%, it exhibits good electrocatalytic reduction activity for nitrates.

[0046] Example 8: Preparation of Sr2FeMoO6 catalyst and evaluation of its electrocatalytic activity for nitrate reduction; Sr₂FeMoO₆ catalyst powder was synthesized via a sol-gel method. Sr(NO₃)₂, Fe(NO₃)₃·9H₂O (analytical grade), and (NH₄)₆Mo₇O₆ were weighed in stoichiometric proportions. 24• 4H2O was dissolved in deionized water, and citric acid (CA) and ethylenediaminetetraacetic acid (EDTA) were added as complexing agents; the resulting mixed solution was continuously stirred on a heating table at 200°C until a viscous gel was obtained; the obtained gel was dried in a drying oven at 200°C for 5 hours to completely dry the gel and obtain a fluffy black dry gel; the obtained dry gel was thoroughly ground in a mortar until completely mixed and homogeneous; the ground product was calcined in air at 800°C for 10 hours, and then calcined at 1050°C for 10 hours in a mixed atmosphere of 5% H2 and 95% Ar to obtain the desired Sr2FeMoO6 catalyst powder. Figure 22 The X-ray diffraction (XRD) curves shown indicate the successful synthesis of Ca2FeMoO6 catalyst powder with a double perovskite structure.

[0047] Evaluation of the electrocatalytic reduction performance of the catalyst for nitrate. Electrode preparation and testing procedures were the same as in Example 1. Figure 23 The polarization curves of Sr2FeMoO6 prepared in Example 8 in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution are shown. Figure 24 The product NH4 is obtained from the electrocatalytic reduction of nitrate by Sr2FeMoO6 prepared in Example 8 in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution. + The yield plot shows that, within a certain overpotential range, the yield and Faraday efficiency of Sr₂FeMoO₆ at the optimal potential (-0.8V vs. RHE) are 1.23 mgh. -1 cm -2 (Based on 2.16 mg cm -2 With a catalyst loading of 87.76%, it exhibits good electrocatalytic activity for the reduction of nitrates.

[0048] Example 9: Preparation of Ba2FeMoO6 catalyst and evaluation of its electrocatalytic activity in nitrate reduction; Ba2FeMoO6 catalyst powder was synthesized via a sol-gel method. Stoichiometric amounts of Ba(NO3)2, Fe(NO3)3·9H2O (analytical grade), and (NH4)6Mo7O were weighed separately. 24·4H2O was dissolved in deionized water, and citric acid (CA) and ethylenediaminetetraacetic acid (EDTA) were added as complexing agents. The resulting mixed solution was continuously stirred on a heating table at 200°C until a viscous gel was obtained. The obtained gel was dried in a drying oven at 200°C for 5 hours to completely dry the gel and obtain a fluffy black dry gel. The obtained dry gel was thoroughly ground in a mortar until it was completely mixed and homogeneous. The ground product was calcined in air at 800°C for 10 hours, and then calcined at 1050°C for 10 hours in a 5%H2 / 95%Ar mixed atmosphere to obtain the desired Ba2FeMoO6 catalyst powder. Figure 25 The X-ray diffraction (XRD) curves shown indicate the successful synthesis of Ca2FeMoO6 catalyst powder with a double perovskite structure.

[0049] Evaluation of the electrocatalytic reduction performance of the catalyst for nitrate. Electrode preparation and testing procedures were the same as in Example 1. Figure 26 The polarization curves of Ba2FeMoO6 prepared in Example 9 in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution are shown. Figure 27 The product NH4 is obtained from the electrocatalytic reduction of nitrate by Ba2FeMoO6 prepared in Example 9 in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution. + The yield plot shows that, within a certain overpotential range, the yield and Faraday efficiency of Ba₂FeMoO₆ at the optimal potential (-0.4V vs. RHE) are 4.96 mgh. -1 cm -2 (Based on 2.16 mg cm -2 With a catalyst loading of 97.6%, it exhibits excellent electrocatalytic reduction activity for nitrates.

[0050] Evaluation of the electrocatalytic nitrate reduction catalytic activity of the commercial Fe2O3 catalyst compared to Example 1; Figure 28 The X-ray diffraction (XRD) curve of commercial Fe2O3 is shown.

[0051] Commercial Fe2O3 catalysts and LaFeO 3-δ The catalyst was prepared as an electrode and its electrocatalytic activity for nitrate reduction was tested under the same conditions. Figure 29 The polarization curves of commercial Fe2O3 in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution are shown in Comparative Example 1. Figure 30 As shown in Comparative Example 1, the product NH4 is obtained from the electrocatalytic reduction of nitrate by commercial Fe2O3 in 0.1 mol / L KOH solution and 500 mg / L KNO3 solution. +The yield diagram shows that, within a certain overpotential range, the yield and Faraday efficiency of commercial Fe2O3 at the optimal potential (-0.4V vs. RHE) are 0.288 mgh. -1 cm -2 and 69.55%.

[0052] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements can be made without departing from the principle of the present invention, and these improvements should also be considered within the scope of protection of the present invention.

Claims

1. A class of iron-based perovskite oxides characterized in that, The molecular formula of the perovskite oxide is ABO 3-δ (0≤δ≤1) and AA'BB'O6; wherein ABO 3-δ The A site of the perovskite oxide of the type ABO (0≤δ≤1) is composed of rare earth or alkali metal elements, and the B site is composed of iron elements; the A and A' sites of the perovskite oxide of the type AA'BB'O6 are respectively composed of rare earth elements and alkali metal elements, the B site is iron elements, and the B' site is molybdenum elements.

2. The iron-based perovskite oxide according to claim 1, characterized by, The perovskite oxide has a formula AB0 3-δ (0≤δ≤1); wherein the A-site element is preferably La and Sr; the B-site element is Fe; the double perovskite oxide has a formula AA'BB'O6; wherein the A-site element is preferably La, Pr, Nd, Sm, Gd; A' is preferably Ca, Sr, Ba, and the B-site element is Fe; and the B' site element is Mo.

3. The iron-based perovskite-type oxide according to Claim 1, characterized by: The perovskite type oxide has a molecular formula of LaFeO 3-δ 0.8 0.2 3-δ 0.6 0.4 3-δ 0.4 0.6 3-δ 0.2 0.8 3-δ 3-δ 0.5 0.5 3-δ 0.5 0.5 3-δ 0.5 0.5 3-δ 0.5 0.5 3-δ 0.5 0.5 3-δ 5+δ 5+δ Ca2FeMoO6, Sr2FeMoO6and Ba2FeMoO6.​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​ 4. The method of producing the iron-based perovskite oxide according to any one of claims 1 to 3, characterized by, The method is prepared according to stoichiometric ratio by solid phase reaction method, sol-gel method, coprecipitation method, combustion method, hydrothermal method or microwave method.

5. The method of producing an iron-based perovskite oxide according to any one of claim 4, characterized by, The method is prepared by sol-gel method.

6. The method of making an iron-based perovskite oxide according to any one of claims 5, wherein The sol-gel method comprises: dissolving nitrate of A-site element and nitrate of B-site element or ammonium molybdate in deionized water according to stoichiometric ratio, adding citric acid (CA) and ethylenediaminetetraacetic acid (EDTA), heating and stirring until a viscous colloidal substance is obtained, heating and drying the colloidal substance to obtain fluffy xerogel, and grinding and calcining.

7. The method of making an iron-based perovskite oxide according to any one of claims 6, wherein the method further comprises the step of: The heating and drying temperature of the colloidal substance is 200 DEG C, and the drying time is 5h.

8. The method of making an iron-based perovskite oxide according to any one of claims 7, wherein, The calcination temperature in air is 800-1100 DEG C, and the calcination time is 5-10h; for the AA'BB'O6 type perovskite oxide, further calcination is carried out in 5%H2 / 95%Ar mixed atmosphere at 600-1100 DEG C for 4-10h.

9. Application of the iron-based perovskite oxide according to any one of claims 1-3 in electrocatalytic reduction of nitrate to synthesize ammonia.